2012
DOI: 10.1002/cae.21564
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a new approach for the design of an e‐learning platform in engineering education

Abstract: Modern corporations, institutions, universities and schools consider e‐education as a way of educating larger groups of students in less time and of reducing the use of various resources. Since setting up a web‐system for e‐education requires a significant amount of time, as well as the necessity of having a computer and other resources, the assessment of the goals and desired effects of the online system should be made in the preparation phase. It is important to highlight that only putting course contents on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 40 publications
3
51
0
Order By: Relevance
“…In the meantime, quality deployment function (QFD) may provide a foundation from both educational and industrial perspectives and from a knowledge system view point [17][18][19][20][21][22], and QFD is applied in engineering education in order to translate key requirements for the field into an effective curriculum and to enhance instructional quality [17,[23][24][25]. The same research may have identified a lack of integration between BIM and other supportive curriculum areas [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, quality deployment function (QFD) may provide a foundation from both educational and industrial perspectives and from a knowledge system view point [17][18][19][20][21][22], and QFD is applied in engineering education in order to translate key requirements for the field into an effective curriculum and to enhance instructional quality [17,[23][24][25]. The same research may have identified a lack of integration between BIM and other supportive curriculum areas [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it can make a single course into a multi-disciplinary integration the teaching platform [4][5] .…”
Section: Teaching Content Reformationmentioning
confidence: 99%
“…Different authors (Duart & Sangrà, 2000;Espinosa, 2000;Lally, 2000;Sagrà, 2001;Rourke & Anderson, 2002;Fernández, 2003;Cabero, 2006;Martínez, Sampedro, Péres, Miláns del Bosch & Granda, 2008;Ballesteros, Cabero, Llorente & Morales, 2010;Fustes, Díaz & Entonado, 2010;García & Cabero, 2011;Del Moral & Villalustre, 2012;etc. ), have studied this aspect and, in 2008, the first standard on the quality of virtual learning was defined, the une 66181:2008 standard (Hilera González, 2008), since simply uploading course content onto the web, without using the appropriate teaching models and principles, without adequate means of communication between the participants and the educators and without making proper use of information technologies to present the content of the course, is not sufficient to achieve the educational ends, as Violante & Vezzetti (2014) suggest. On this basis and, as we consider it to be essential that all of the elements that make up virtual learning be contemplated and studied to ensure its quality, we have undertaken the study presented here.…”
Section: Introductionmentioning
confidence: 99%